The Theory and Application of Microeconomics in Companies, especially in the Field of Private Medicine, as well as the Interfaces to Artificial Intelligence - Tetik, Murat, 1972-
Rozbor účinkov používania umelej inteligencie v sektore zdravotnej starostlivosti so zameraním na mikroekonomické a sociálne aspekty.